Smart Cities in the Era of Globalisation - Mukesh Kumar Mishra (ZBW – Leibniz Information Centre for Economics, 2020)
The world is in the midst of a massive wave of urban growth. World is urbanizing rapidly, and this can bring negative consequences to the environment. Against this backdrop, governments are looking for ways to ensure cities' environmental sustainability. An urbanizing world means cities are gaining greater control over their development, economically and politically. Cities are also being empowered technologically, as the core systems on which they are based become instrumented and interconnected, enabling new levels of intelligence. In parallel, cities face a range of challenges and threats to their sustainability – across their business and people systems and core infrastructures such as transport, water, energy and communication – that they need to address holistically. To seize opportunities and build sustainable prosperity, cities need to become “smarter.” At the same time, it has been noted that residents of cities and their surrounding environments are increasingly connected through intelligent or smart technologies.
Keywords: O18; O19; 330; Smart Cities; Smart Economy